EFFICIENT RESOURCE UTILIZATION AND MANAGEMENT MECHANISMS FOR DEVELOPING LIVESTOCK FARMING IN DESERT-PASTURE AREAS - Nurmanov Sherzod Khujayarovich (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2026)
The development of livestock farming in desert-pasture areas through efficient resource utilization and management mechanisms is one of the most pressing directions of Uzbekistan’s agrarian policy. The study analyzes over 21 million hectares of desert and semi-desert pastures, their degradation (over 40%), the impact of climate change, and anthropogenic pressure. It proposes mechanisms for efficient resource use through geobotanical monitoring, NDVI assessment, rotational grazing systems, and the establishment of high-yield agrofitocenoses with drought-resistant plants (saxaul, cherkez, izen, etc.). The results show that these approaches increase pasture productivity by 10%, save water resources (e.g., 1.375 million m³ for 500 sheep), sharply boost livestock productivity, and generate economic benefits of 112.5–540 million UZS. The integration of digital monitoring (“Geo Pasture” app), state policy (Presidential Decrees), and economic incentives (clustering, subsidies) ensures ecological sustainability and food security.